2016
DOI: 10.1002/2015gc006128
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical behavior of dissolved manganese in the East China Sea: Seasonal variation, estuarine removal, and regeneration under suboxic conditions

Abstract: To better understand the geochemical cycle of dissolved manganese (Mn) in the East China Sea (ECS), the distribution of dissolved Mn across the ECS was investigated during three field studies in 2011 (May, August, and November). The concentration of dissolved Mn decreased across the ECS with distance from the coast. Mn‐rich ECS shelf waters could export to the Kuroshio Waters, and had the potential to influence the northwest Pacific Ocean as well as the Japan Sea. The Kuroshio Waters were devoid of dissolved M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 70 publications
(100 reference statements)
1
14
0
Order By: Relevance
“…The nitrate concentration and fluxes increased by about tenfold from 1968 to 1997 [ Yan et al ., ; Duan et al ., ]. This agrees with the high nutrient concentration found around the Yangtze River estuary, and this distribution pattern has been observed repeatedly [ Liu et al ., ; Wei et al ., ]. However, the low level of dissolved metals around the Yangtze River estuary indicates that, although highly polluted, the Yangtze River is not a significant source for dissolved trace metals.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The nitrate concentration and fluxes increased by about tenfold from 1968 to 1997 [ Yan et al ., ; Duan et al ., ]. This agrees with the high nutrient concentration found around the Yangtze River estuary, and this distribution pattern has been observed repeatedly [ Liu et al ., ; Wei et al ., ]. However, the low level of dissolved metals around the Yangtze River estuary indicates that, although highly polluted, the Yangtze River is not a significant source for dissolved trace metals.…”
Section: Resultssupporting
confidence: 86%
“…With the building of trace metal clean laboratories, and use of Teflon and LDPE containers and labware, trace metal clean sampling and analytical protocols can be applied, and more credible data have been reported. Dissolved Al and Mn distribution in the Yellow Sea (YS) and East China Sea have been studied by Ren et al [2011] and Wang et al [2016]. Wang et al [2012] have examined the behavior of several dissolved metals (Cu, Cd, and Mn) in the Pearl River estuary.…”
Section: Introductionmentioning
confidence: 99%
“…The vertical distribution of Mn also excludes a sedimentary source of Fe to the surface ocean at 35°N. Both Mn and Fe are released from reductive sediments (29,30), so the marked differences between the vertical (Fig. 4) and surface (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…4) and surface (Fig. 1) distributions of Fe and Mn indicate independent sources, even accounting for their different redox behavior, biological removal, and cycling (29)(30)(31). Thus, based on these multiple lines of evidence we attribute the elevated Fe concentrations observed between 35°N and 40°N to recent aerosol deposition.…”
Section: Resultsmentioning
confidence: 99%
“…The Fe‐Mn fraction is the most Pb‐reactive particulate phase, and the decrease in the oxidation‐reduction potential of sediment leads to a solubilization of Pb associated with Fe‐Mn oxides; part of it precipitates immediately, while the other part diffuses to the overlying water (Elbaz‐Poulichet et al, ). Studies of dissolved Mn in this area revealed an increased factor of 2–11 during the low‐oxygen cruise in 2011 (Wang et al, ), while the release of DPb was not as significant. Moreover, the bottom of Station A3 suffers high salinity intrusion, and there was no significant increase in DPb compared with same water masses.…”
Section: Discussionmentioning
confidence: 96%